Limb salvage procedures in osteosarcomas around the knee joint - Merchán, Emérito Carlos Rodriguez; Herrera, Salvador Sánchez; Lopez, Jose Manuel Gonzalez (São Paulo Medical Journal, 1994)
Surgical techniques developed for restoring skeletal continuity after a local resection of a bone tumor (limb salvage procedures) revolutionized the management of the patient suffering from osteosarcomas around the knee. In this article the authors review the current status of various reconstruction procedures; they include osteoarticular allograft arthrodesis, rotation plasty, expandable prosthesis and knee arthroplasty. In summary they suggest that the knee arthrodesis is the preferred procedure for young and active patients, the rotation plasty should be recommended as the alternative to amputation for very young patients, and the customized prostheses are preferred for patients with limited longevity.